Métodos quimiomecânicos no tratamento de lesões cariosas profundas: um estudo in vitro - Luiza de Almeida Queiroz Ferreira (2021)
This work aimed to investigate the antimicrobial properties of substances used in chemo mechanical methods and their effects on dentin and pulp cells. An artificial caries lesion was developed in standardized cavities performed in bovine teeth with strains of Streptococcus mutans (ATCC 25175) and Lactobacillus casei (ATCC 7463). The cavities were treated according to the following groups: G1 - Phosphate Buffer Saline (PBS); G2 - Chlorhexidine (CHX); G3 – Papacárie®; G4 - Ozonized water (O3) and G5 - Photodynamic Therapy (PDT). A microbial sample was collected, diluted, and cultivated to obtain isolated colonies through pour-plate technique. The activity of dentin gelatinase metalloproteinases (MMP-2 and MMP- 9) was qualitatively evaluated by zymography assay. Cell viability was evaluated in pulp cells after 24, 72, and 120h and osteodifferentiation after 10 days. CHX and PDT caused bacterial reduction compared to the other groups (p<0.05). PBS, CHX, and PDT showed gelatinolytic activity through the expression of MMP-2 and MMP-9. Cell viability was reduced at 120 h for all groups in comparison to control. CHX, O3, and PDT induced greater osteodifferentiation ® compared to PBS and Papacárie . It was concluded that CHX and PDT promoted a slight decrease in bacterial load in the artificial carious lesion. All treatments caused, in part, gelatinolytic activity, through the expression of MMP-2 and MMP-9. Despite decreasing cell viability, no treatment interfered with the differentiation of pulp cells. The use of chemo mechanical methods has a slight biological significance in reduction of bacterial load in artificial carious lesions. In addition, some of these treatments can activate metalloproteinases and interfere with essential pulp cell functions.